Flow metering basics - Megat Mohd Noor, Megat Johari (1987)
This topic presents an overview of the various methods used to measure wastewater. It will cover both pressurised conduits and open channels. The discussion will also cover end-of-pipe measurements, the use of weirs and flumes, instantaneous measurement and continuous flow metering. The applicability of each method regarding flow ranges and wastewater characteristics will also be discussed.